Delayed VEGF Treatment Enhances Angiogenesis and Recovery After Neonatal Focal Rodent Stroke - Dzietko, M. (2013)
Neonatal stroke occurs in one in 4,000 live births and leads to significant morbidity and mortality. Approximately two thirds of the survivors have long-term sequelae including seizures and neurological deficits. However, the pathophysiological mechanisms of recovery after neonatal stroke are not clearly understood, and preventive measures and treatments are nonexistent in the clinical setting. In this study, we investigated the effect of vascular endothelial growth factor (VEGF) treatment on histological recovery and angiogenic response to the developing brain after an ischemic insult. Ten-day-old Sprague–Dawley rats underwent right middle cerebral arterial occlusion (MCAO) for 1.5 h. Diffusion-weighted MRI during occlusion confirmed focal ischemia that was then followed by reperfusion. On group of animals received 5-bromo-2-deoxyuridine and sacrificed at postnatal day (P)18 or P25. A second group of animals was treated with VEGF (1.5 µg/kg, icv) or phosphate-buffered saline (PBS) at P18 and perfusion fixed at P25. Based on Nissl and iron staining, a single VEGF injection reduced the injury score, compared to the animals that underwent MCAO and PBS injection. Furthermore, neurodegeneration represented by neuronal nuclei staining was markedly diminished. In addition, animals treated with VEGF revealed a positive trend in endothelial proliferation and a significant increase in total vessel volume in the peri-infarct region of the caudate. The number of Iba1-positive microglial cells was significantly reduced after a single VEGF injection, and myelin basic protein expression was enhanced in the caudate after ischemia without an effect of VEGF treatment. In conclusion, delayed treatment with VEGF ameliorates injury, promotes endothelial cell proliferation, and increases total vascular volume following neonatal stroke. These results suggest that VEGF has a neuroprotective effect, in part by enhancing endogenous angiogenesis. These data contribute to a better understanding of neonatal stroke.